2014
DOI: 10.2337/dc13-2365
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Rate of Weight Gain During Early Adulthood With the Prevalence of Subclinical Coronary Artery Disease in Recently Diagnosed Type 2 Diabetes: The MAXWEL-CAD Study

Abstract: OBJECTIVETo investigate the association of the rate of weight gain (Rate max_wt ) between the age of 20 years and the age of maximum lifetime weight gain with indicators of subclinical coronary artery disease (CAD) at the time of diagnosis of type 2 diabetes (T2D). RESEARCH DESIGN AND METHODSWe studied 1,724 consecutive Korean subjects aged ‡30 years with recently diagnosed (within 3 months) T2D and one or more cardiovascular risk factors to investigate the association of Rate max_wt with subclinical CAD. We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…As the structure of plaques are complex, the accurate mechanism of coronary plaque progression have not yet been proved but may be dependent on plaque composition, cardiovascular risk profile and level of inflammatory activation. 10,[36][37][38] Lehman et al 38 found that the differences in the rate of progression are dependent on plaque composition and that this progression may be greater for NCP compared with CP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the structure of plaques are complex, the accurate mechanism of coronary plaque progression have not yet been proved but may be dependent on plaque composition, cardiovascular risk profile and level of inflammatory activation. 10,[36][37][38] Lehman et al 38 found that the differences in the rate of progression are dependent on plaque composition and that this progression may be greater for NCP compared with CP.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 The literature regarding coronary artery disease and coronary plaque morphology in patients with newly diagnosed T2D is sparse. 10,11 Contrast-enhanced coronary computed tomography angiography (CCTA) has evolved as a robust imaging modality for ruling out significant coronary artery disease. 12,13 Moreover, CCTA permits detailed non-invasive coronary plaque assessment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this finding may be that diabetic patients are prone to arteriosclerosis, even in the early stages of the disease, and are likely to have advanced coronary disease when they start taking medication to help manage their diabetes. It is known that patients with type 2 DM and obesity are prone to coronary artery stenosis, even in the early stage of type 2 DM [27]. It is also known that patients with a longer duration of type 2 DM have more advanced coronary artery stenosis than those with a shorter disease duration [28].…”
Section: Discussionmentioning
confidence: 99%
“…5). Thus, attention should also be paid to obesity early in life and to the rate and speed of weight gain 13. Rapid weight gain causes insulin resistance, increases inflammatory responses, and raises blood sugar and blood pressure, fundamentally damaging intravascular endothelial cells, which could cause coronary artery disease.…”
Section: Maintain the Recommended Caloric Intake For A Healthy Dietmentioning
confidence: 99%